Effectiveness of Motor Skills Learning Model through Sports Games for Madrasah Ibtidaiyah Students - Bahtiar Firdiansyah; Valentino Hary (Gladi : Jurnal Ilmu Keolahragaan, 2023)
Abstract This study aims to determine the motor skills learning model based on sports games as well as to test its effectiveness in improving the motor skills of elementary school (madrasah ibtidaiyah). This development research adopts the ADDIE model development and uses mixed methods, qualitative data was obtained from the description of the model, and quantitative data were obtained from field effectiveness tests. The subjects included in the development of the model were 60 underclass students 6-8 years in Kudus. Retrieval of research data using tests of motor skills learning outcomes for madrasah ibtidaiyah with validity and reliability values are categorized "good". A pre-post test was carried out for further analysis using the SPSS-23 paired sample t-test. The significance value of the difference in the t-count that appears = 16.56 df = 59 and p-value = 0.00 <0.05, there is a significant difference before and after being given the treatment of the developed model. They concluded that the model developed is in the form of 21 motor skills learning items consisting of 6 major criteria based on recorded sports games along with the procedures for implementing each item. The developed model can significantly improve motor skills learning outcomes for madrasah ibtidaiyah students.